2014
DOI: 10.17268/agroind.science.2014.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different proportions of citrus fruit pulp in the sensory acceptability of a fermented drink and protein made from whey residual

Abstract: RESUMENEl presente estudio se elaboró una bebida láctica fermentada con de pulpa de naranja, carambola y maracuyá, a partir de lactosuero dulce proveniente de la industria de elaboración de queso fresco. En la formulación de la bebida se utilizó 75% de lactosuero y el 25% restante fue una mezcla de las tres frutas anteriormente mencionadas. Para obtener las proporciones se utilizó un diseño de mezclas del tipo Simplex con centroide ampliado. Se evaluó la aceptabilidad sensorial a través de 38 jueces no entrena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
1
Order By: Relevance
“…Linares et al [15] showed similar results in the physico-chemical characterization of sweet whey samples, obtaining a pH of 6.84; acidity titrated of 0.11% (% lactic acid); protein between 0.6 and 1%; and ash 0.6%. De Paula et al [16] performed a physico-chemical characterization of whey obtained from the manufacture of coastal cheese.…”
Section: Whey Physico-chemical Characterizationmentioning
confidence: 62%
See 1 more Smart Citation
“…Linares et al [15] showed similar results in the physico-chemical characterization of sweet whey samples, obtaining a pH of 6.84; acidity titrated of 0.11% (% lactic acid); protein between 0.6 and 1%; and ash 0.6%. De Paula et al [16] performed a physico-chemical characterization of whey obtained from the manufacture of coastal cheese.…”
Section: Whey Physico-chemical Characterizationmentioning
confidence: 62%
“…On the other hand, Linares et al [15] evaluated the effect of different proportionsofcitruspulpon the sensorial acceptability of a fermented and protein drink made from residual whey. For this p u r p o s et h e yu s e dal y o p h i l i z e dl a c t i cc u l t u r eo fS.…”
Section: Microbial Cultures Used To Produce Fermented Beverages Basedmentioning
confidence: 99%
“…Composición de la materia prima.La composición nutritiva aproximada de lactosuero dulce obtenida, concuerda con poca variabilidad con los reportados por Chen et al 24 y Molero et al 25 . Las diferencias son asociadas a la procedencia de la leche, proceso de obtención de suero lácteo y del queso además de condiciones ambientales que afectan directamente las características físico-químicas de la leche y por consiguiente del lactosuero 26 .…”
Section: Discussionunclassified